2000
DOI: 10.1088/0953-8984/12/37/307
|View full text |Cite
|
Sign up to set email alerts
|

Strain energy density in the x-ray powder diffraction from mixed crystals and alloys

Abstract: A correlation between precise x-ray powder diffraction patterns and atomic size mismatch in disordered mixed crystals (alloys and ionic crystals) is observed. The anisotropy of the elastic moduli has been taken into account for evaluation of the strain energy density of the mixed crystals revealed in x-ray powder diffraction measurements. The precursor of the phase transformation for a quenched disordered Au-Cu alloy is identified. § Present address:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 12 publications
(18 reference statements)
5
45
1
Order By: Relevance
“…This method defines the crystallite size in terms of a mean effective size of the coherently scattering region normal to the reflecting planes [35]. The Scherrer relation between crystallite size and integral breadth is given by:…”
Section: Scherrer Methodmentioning
confidence: 99%
“…This method defines the crystallite size in terms of a mean effective size of the coherently scattering region normal to the reflecting planes [35]. The Scherrer relation between crystallite size and integral breadth is given by:…”
Section: Scherrer Methodmentioning
confidence: 99%
“…We suggest that these three methods are also suitable models for the evaluation of the crystallite size of ZnO nanoparticles. Rosenberg et al [28] observed that for metallic samples with cubic structures, the uniform deformation energy model is suitable. We have made a comparison of the estimated microstrain e values of ZnO nanoparticles annealed at 450°C reported by Dole et al [29] by W-H models, with that of our present values.…”
Section: Size-strain Plot (Ssp)mentioning
confidence: 99%
“…However, in nanoparticles the strain is not uniform in all directions, so uniform stress deformation model & uniform energy density deformation model take into account of the anisotropic nature of Young modulus of the crystal and are hence more realistic [29]. The isotropic lattice strain, ε hkl in UDM is replaced σ/E hkl , where E hkl is the young modulus in the direction perpendicular to the set of planes (hkl).…”
Section: Uniform Stress Deformation Modelmentioning
confidence: 99%